Organic Matter Inputs by Selected Cropping Systems on a Vertisol in the Semi-arid Tropics of India - Abdurahman, M D; Seeling, B; Rego, T J; Reddy, B Bhaskar (Annals of Arid Zone, 2016)
Soils of the Semi-Arid Tropics (SAT) are often low in organic matter. Concern about the maintenance of organic matter levels under conditions of intensified land-use makes knowledge of organic matter returns to soil by different crops and cropping systems important. In a two year field experiment, organic matter inputs of cropping systems for the SAT were studied on a deep Vertisol. When the crops were not fertilized, Sorghum/Pigeonpea intercrop system for two years ( S/PP S/PP) had higher root organic matter than the non-legume system of Sorghum, followed by Safflower for two years ( S+SAF S+SAF). But, when the crops were fertilized. the non-legume system also gave fairly high root organic matter. The lowest root organic matter inputs were found in the traditional Fallow + Sorghum Fallow + Chickpea (F+S F+CKP) system. Most of the root organic matter was produced in the upper 0-30 cm layer. In addition, pigeonpea dropped around 3 t ha -1 a -1 of dry leaves. Cowpea also dropped dry leaves, but its contribution was only around 140 kg ha -1 a -1. The improved S/PP S/PP and CowpealPiegonpea intercrop COW/PP S+SAF systems provided much higher organic matter inputs than the improved non-legume systems (S+SAF S+SAF), even where organic matter inputs of the latter were increased through fertilization. But, all improved systems were considerably better than the traditional system (F+S F+CKP). We concluded that longer crop cover, and greater biomass of improved cropping systems. have the potential to increase organic matter content over that of the traditional system. Particularly. the dropping of leaves by pigonpea after flowering increased organic matter addition in a situation where traditionally, all above-ground biomass is removed from the field.